An integrated literacy/science intervention for English language learners in third grade - Davis, Amy D. (Kansas State University, 2018)
English language learners (ELLs) are expected to meet the same academic standards as those of their fluent English-speaking peers while simultaneously acquiring a second language. When content area instruction is embedded with literacy-based tasks, ELLs' achievement is both the acquisition of content area knowledge and English language skills can be anticipated. Science is a content area that can provide a deep context for ELLs to develop academic language because students must use their literacy skills to gather information about scientific concepts. The purpose of this study was to investigate the impact of an instructional intervention integrating literacy-based practices in science on third grade ELLs' science achievement and English language development. The mixed methods study was conducted at an elementary school in the Midwest, United States. There were 12 participants, eight identified as ELL and four fluent English speakers. Four of eight identified as ELL received the intervention while the remaining four ELL and fluent English speakers were instructed by the classroom teacher. The intervention was based on the systematic and repeated practice of language strategies and explicit vocabulary instruction. Authentic communication was used during scientific inquiry, discussions, and the reading of expository science text. Both quantitative and qualitative data was collected from pre and posttest data from five FOSS I-Check assessments, researcher's observations and field notes, participants' artifacts such as science journal entries and reflections, classroom teacher interview, and recorded session videos. The data was coded and analyzed identifying major themes which are noted in the findings. The results concluded the four participants who received the intervention outperformed their ELL peers not receiving the intervention but were still slightly behind their English-speaking peers. Overall, the participants receiving the intervention showed gains in their productive language as reflected in their utilization of domain-specific vocabulary in their speaking and writing. The conclusions drawn from this study included ELLs can benefit from receiving an integrated literacy/science intervention in both their acquisition of scientific knowledge and language development.
Keywords: English language learners; literacy/science intervention; science achievement for ELLs; scientific inquiry; language strategies